Podemos conversar? Uma análise sobre a estrutura conversacional e o interlocutor invisível nos podcasts - Gui, Ana Maria de Souza (Universidade Federal de São Carlos, 2024)
This work aims to analyze the activation of conversational strategies for audience engagement and connection in the scientific linguistics outreach podcast, 'Mexendo com a Língua' ('Playing with Language'). By using conversational elements, triggers used by the podcast hosts and interviewees to interact with their listeners will be observed. Through this study, possible benefits of this practice will be discussed.
Can we talk? An analysis of conversational structure and the invisible interlocutor in podcasts
Keywords: Linguística; Pragmática; Análise da conversação; Podcast; Linguistics; Pragmatics; Conversational analysis; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA